Pengaruh Pemberian Pupuk Kalsium terhadap Pertumbuhan dan Produksi Tanaman Kedelai (Glycine max (L.) Merr.) - Friska, M; Amnah, R; Wahyuni, SH; Handayani, S; Nasution, J; Harahap, P; Siregar, EA; Aziz, A (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Fiska M, Amnah R, Wahyuni SH, Hadayani S, Nasution J, Haraha P, Siregar EA, Aziz A. 2022. Effect of calcium on growth and production of soybean plants (Glycine max (L.) Merr.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 871-877. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Soybean is one of the legume crops and is the world's main source of protein and vegetable oil. Calcium is one of the essential elements needed by plants for growth and production. The purpose of this study was to determine the effect of calcium fertilizer on the growth and production of soybeans. This research was carried out from November 2020 to February 2021. The method in this study was a non-factorial randomized block design (RAK) with 4 types of calcium fertilizer treatments: 0 g/polybag (C0), 0.375 g/polybag (C1), 0.525 g/polybag (C2) and 0.865 g/polybag (C3). The results showed that calcium fertilizer had an effect on the number of pods, weight of pods, weight of filled pods, and weight of seeds. The calcium fertilizer treatment that gave the best results on the growth and production of soybeans was found in the C2 treatment at a dose of 0.525 g.